Answer:
I need info
Step-by-step explanation:
Equivalent equations are equations that have the same value
The equation in logarithmic form is ![t = \frac{\log(9)}{2}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B%5Clog%289%29%7D%7B2%7D)
<h3>How to rewrite the equation</h3>
The expression is given as:
![10^{2t} = 9](https://tex.z-dn.net/?f=10%5E%7B2t%7D%20%3D%209)
Take the logarithm of both sides
![\log(10^{2t}) = \log(9)](https://tex.z-dn.net/?f=%5Clog%2810%5E%7B2t%7D%29%20%3D%20%5Clog%289%29)
Apply the power rule of logarithm
![2t\log(10) = \log(9)](https://tex.z-dn.net/?f=2t%5Clog%2810%29%20%3D%20%5Clog%289%29)
Divide both sides by log(10)
![2t = \frac{\log(9)}{\log(10)}](https://tex.z-dn.net/?f=2t%20%3D%20%5Cfrac%7B%5Clog%289%29%7D%7B%5Clog%2810%29%7D)
Apply change of base rule
![2t = \log_{10}(9)](https://tex.z-dn.net/?f=2t%20%3D%20%5Clog_%7B10%7D%289%29)
Divide both sides by 2
![t = \frac{\log_{10}(9)}{2}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B%5Clog_%7B10%7D%289%29%7D%7B2%7D)
Rewrite as:
![t = \frac{\log(9)}{2}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B%5Clog%289%29%7D%7B2%7D)
Hence, the equation in logarithmic form is ![t = \frac{\log(9)}{2}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B%5Clog%289%29%7D%7B2%7D)
Read more about logarithms at:
brainly.com/question/25710806
Answer:
-9
Step-by-step explanation:
The sum of -2 and -7 is given as follows;
-2 + (-7)
In mathematical operations, + * - is -.
So we have;
-2 - 7
This gives us: -9
Answer:
3
Step-by-step explanation:
Those are factors of 9 not multiples
Results in the most extreme 5% of possible outcomes
Hope this helps :)